ALIH KODE DALAM LIRIK LAGU BINGO! OLEH AKB48 - Nandha, Mega (Humanis, 2016)
The title of this research is Code Switching in the Song Lyric of BINGO! by AKB48. Code switching is code switch and mix between a language with the other language. It is not only occurred in the conversation, but also in the song lyric. This research is analyzed to find out how code switching is used based on tag switching, intrasentential switching, and intersentential switching. The data source used in this research are obtained from a song lyric of BINGO! by AKB48. AKB48 is the popular girlband from Japan. They are have six albums, and the most album which has many of code switching is Set List Greatest Songs. Within that album, BINGO! is the one and only song that has tag switching, intrasentential switching, and intersentential switching. As a result, in the song lyric of BINGO! has 16 code switching that are founded. There are five data are tag switching, eight data are intrasentential switching, and three data are intersentential switching.
Keywords: code switching, tag switching, intrasentential switching, intersentential switching, song lyric